THE APPLICATION OF NURSING THEORY “SELF CARE OREM” IN NURSING CARE OF MULTIPAROUS PREGNANCY WITH ANAEMIA: A CASE REPORT - Siti Nurbayanti Awaliyah; Setyowati S; Tri Budiati (Journal of Maternity Care and Reproductive Health, 2018)
Anemia in pregnancy is a major concern of health problem during pregnancy, as it is associated with the increase of maternal and infant morbidity and mortality cases. Multiparous pregnant women have a higher risk of anemic during their pregnancies. The nurse specialist of maternity has the crucial roles to help multiparous pregnant women with anemia in filling their basic needs due to various nursing problems. Methodology in this article used the case studies approach on seven multiparous pregnant women with anemia. Several nursing issues emerged are the risk of injury both to the mother and to the fetus, dizziness, limited activities and limited knowledge of anemia.  The self-care theory focused on an individuals’ ability to fill their self-needs by paying attention to the level of dependent care. The application of self-care theory is suitable for multiparous pregnant women with anemia as it helps them to be independent patients. Nurses may use the Orem framework as a guide in conducting the nursing process.Keywords: anemia, multiparous pregnant women, self-care